Encouraging sustainable modal shift—An evaluation of the Portsmouth Big Green Commuter Challenge. Issue 1 (March 2017) - Wall, Graham; Olaniyan, Bukola; Woods, Lee; Musselwhite, Charles
Highlights: This work discusses the findings of a "smarter choice" travel behaviour case study in Portsmouth. There were 928 participants involved representing 33 organisations. Mileage for all modes of travel was reduced by 6%. Estimated emissions per mile were reduced (CO2 by 46% and NOx by 17%). Abstract: This paper describes the impact of the Portsmouth "Big Green Commuter Challenge" (BGCC) event, organised by Portsmouth City Council (PCC) in order to reduce carbon and nitrogen oxide emissions from transport within the city. In total, over 900 people and 33 organisations took part in the 2011 event. This is an example of a "Smarter Choice" measure designed to encourage travel behavioural change to more sustainable modes of transport. A literature review and evaluation of previous "Smarter Choices" measures has been carried out to give some context to the BGCC. An introduction to the city of Portsmouth is presented, in particular its efforts to reduce road traffic and emissions from the city centre area. The event encouraged a modal shift to more sustainable modes of travel, resulting in estimated reductions in CO2 and NOx emissions per mile. However, a number of further recommendations have been made to enable future similar events to have a greater impact on road traffic and emissions.